Impact of situational awareness attributes for resilience assessment of active distribution networks using hybrid dynamic Bayesian multi criteria decision-making approach. (December 2022) - Sonal,; Ghosh, Debomita
Highlights: The main contributions of the paper are as follows: to frame a comprehensive multi-level hierarchy model using linguistic scale based multi criteria decision-making (MCDM) approach for situational awareness (SA) oriented resilience level assessment of active distribution network (ADN) against different types of high impact low frequency (HILF) events. To determine the key contributing factors of source uncertainty, with a focus on analysis of uncertain ADN availability leading to non-deterministic resilience (NDR), using a hybrid MCDM-dynamic Bayesian network (DBN) approach. To illustrate the significance of PDF in NDR and quantify operational performance of ADN to withstand critical loads due to NDR in terms of load not served (LNS) index. Analysis of the proposed technique on IEEE 33-bus network to demonstrate the efficacy of the approach. Abstract: The planning and operation of distribution systems have significantly changed due to the extensive osmosis of ICT (information and communication technologies) into power systems. Load growth, together with increased power quality expectations by the customers, has transformed the conventional distribution network to active distribution network (ADN), with penetration of distributed energy resources (DERs). This has imposed the necessity to analyze resilient performance of ADN subjected to the boon of ICT for enhanced situational awareness (SA). This paper focuses on a detailed multi-level hierarchy framework using linguistic scale based multi-criteria decision-making (MCDM) approach for SA oriented resilience level estimation of ADN, considering different high impact low frequency (HILF) events. The rapidly changing environmental conditions and ambiguity in interaction of network parameters lead to non-deterministic resilience (NDR), thus, affecting the operational resilience of ADN on a daily basis. To analyze the uncertain ADN availability due to NDR, hybrid MCDM-dynamic Bayesian network (DBN) approach is used. For better decision-making, the operational performance of ADN, to withstand critical loads due to NDR is analyzed in terms of load not served (LNS) index. The proposed framework is tested on IEEE 33-bus distribution network.